Improving the optical and electroactive response of poly(vinylidene fluoride–trifluoroethylene) spin-coated films for sensor and actuator applications - Cardoso, V. F. (2012)
Poly(vinylidene fluoride–trifluoroethylene), P(VDF–TrFE), thin-films have been processed by spin-coating with controlled thickness. The influence of the thermal annealing and poling conditions on the properties of the material has been investigated. It is shown that thermal annealing strongly influences the microstructure and ferroelectric phase transition of the copolymer but does not significantly affect the degree of crystallinity of the samples. By increasing the annealing temperature, the samples undergo a transition from a microporous to a microfibrillar microstructure, accompanied by a decrease in the gauche defect density within the molecular chains that increases the ferroelectric transition temperature and enthalpy, and also influences the optical transparency of the films, which can achieve transmittances larger that 95% in the visible spectral range. The piezoelectric response of the material can be maximized by increasing the poling temperature at the cost of a decrease in the optical transparency of the film, due to the microstructural changes induced by the electrical field and the temperature. An optical transmittance as high as 90% along the visible spectral range is nevertheless maintained, demonstrating the suitability of the material for electroactive applications where transparency is also a relevant issue.